Healthcare workers’ knowledge and preparedness for unprecedented foodborne botulism outbreak in Saudi Arabia - Abdullah Alhuzaimi; Fatimah S. Alshahrani; Fadi Aljamaan; Fatema H. AL-Ajwad; Ibraheem Altamimi; Abdullah Bukhari; Lama Al-Eyadhy; Sarah Al-Subaie; Nasser S. Alharbi; Mazin Barry; Yamen Shayah; Amr Jamal; et al. (Journal of Infection and Public Health, 2024)
Background: The recent unprecedented foodborne botulism outbreak in Saudi Arabia necessitated an assessment of healthcare workers' (HCWs) knowledge, attitudes, and practices (KAP). This study assessed healthcare workers' knowledge regarding the transmission, contagiousness, presentation, and diagnosis of foodborne botulism, as well as their management practices, including contacting public health authorities, administering antitoxin, preparedness to respond to botulism cases and consulting generative Artificial Intelligent (AI)-chatbots, like ChatGPT. Methods: A cross-sectional online survey targeting Saudi HCWs was conducted from May 6–19, 2024, following the first foodborne botulism outbreak. The survey, developed by infectious disease and public health experts according to the Saudi Public Health Authority (SPHA) botulism guidelines, covered several sections: demographics, knowledge about foodborne botulism, attitudes and perceptions, intended practices, and worry level. Statistical analysis included descriptive statistics, multivariable linear regression to assess factors influencing knowledge, and multivariable logistic binary regression to evaluate factors affecting confidence in handling botulism. Results: Among the 1058 participants, the knowledge score was 9.69/20 (48.4 % correct ± 18 %), with higher scores among HCWs working in tertiary centers, older than 34 years, reading SPHA botulism protocol, and using scientific journals as main information sources. HCWs consulting ChatGPT had significantly lower knowledge scores (p-value < 0.001). HCWs displayed highly intended practices in managing botulism, with a mean score of 4.10/5. The self-rated management confidence was moderate (2.84 ± 1.05 out of 5-points). Multivariable logistic binary regression showed that previous experience with botulism and reading SPHA protocol were the most significant factors associated with a higher management confidence. Conclusions: This study highlights significant HCWs’ knowledge gaps during unprecedented foodborne botulism outbreak. Previous experience with botulism cases and reading recent guidelines were associated with higher knowledge and confidence, while reliance on ChatGPT was linked to lower scores. This study emphasizes the importance of timely publishing local guidelines to favorably affect both knowledge and confidence to deal with infectious outbreaks. Future research should evaluate long-term effectiveness of educational interventions.